The itinerant justice service - Tello Gilardi, Janet (2020)
This article develops a study on itinerant justice carried out by the Judicial Power of Peru, through the Permanent Commission of Access to Justice for People in a Condition of Vulnerability and Justice in your Community in the 34 judicial districts of the country, for the approach of services in the matter of child support, extramarital affiliation, rectification of birth certificates, family violence and designation of supports and safeguards for the benefit of vulnerable populationsthat are geographically distant, with scarce economic resources or in a situation of poverty, in rural and marginal urban areas.